The usage of telemetry measurements methods to determine shaft tube deformations caused by natural and antrophogenic rock mass movements - Jabłoński, Mateusz Pawel; Jaśkowski, Wojciech (Geology, Geophysics and Environment, 2016)
Mining shaft is the most important element of the underground mine. It determines mine’s ability to work efficiently. Mining shaft is used for transporting employees, equipment and dirt or output. It also allows to perform fast rescue operation and ensures that employees in danger can be quickly evacuated. Last but not least it allows ventilation and functioning underground. Mining shaft and especially the shaft tube are subject to influences, both geological and anthropogenic. In details: local geological structure (deposit tectonic structure), mass rock movements due to exploitation inside and outside of safety shaft pillar, underground watercourses and leakages of shaft or voids around the shaft (especially dangerous in case of salt exploitation).Ensuring shaft’s safe operation is the primary aim of measurements and observations performed in mining shafts. This involves not only determining the current technical condition of the mining shaft, but also determining causes of observed changes (Szczerbowski & Jóźwik 2002). In order to preserve the efficiency of every shafts several inventory works have been performed, described in details in Ordinance  (Regulation of the Minister of Economy from 28th of June 2002) and its appendix (Appendix nr 4 to Regulation of the Minister of Economy from 28th of June 2002) (Jaśkowski 2013).The report presents an overview of measurements techniques which are in use in order to perform shift tube’s inventory, with particular emphasis on telemetric measurement methods. Monitoring system designed for ‘Wieliczka’ Salt Mine has been described in details. The system was used in 2014 and 2015 to monitor deformations during sealing and stiffening the shaft housing. Material, injected under considerable pressure (up to 30 MPa) to 92 boreholes located few meters from the shaft, could damage the reinforcement and cause critical failures of the shaft. In order to prevent such situations, mobile system for monitoring the condition of the structure of the shaft was mounted. Its indications allowed to define in the current time the value of deformation occurring in the shaft, and if necessary immediately modify the schedule and course of injection works. Analysis of the results shows a slight deformation of the shaft housing during the injection, and demonstrates the advantages of the monitoring system and a novel method of high-pressure injections (Jaśkowski, Lipecki & Jabłoński 2016).The system and implemented software was created within the project "Developing technologies of sealing mine shafts by Salt Mine ‘Wieliczka’, co-financed by the European Regional Development Fund. Research for the article was funded by statutory research of the Department of Mining Areas Protection, Geoinformatics and Mining Surveying (AGH University of Science and Technology) number 11.11.150.195.